DNA Methylation Profiles in Whole Blood of Huntington's Disease Patients - Zadel, Maja; Maver, Aleš; Kovanda, Anja; Peterlin, Borut (Frontiers in Neurology, 2018)
Epigenetic mechanisms, especially DNA methylation, are suggested to play a role in the age-of-onset in Huntington’s disease (HD) based on studies on patient brains, and cellular and animal models. Methylation is tissue-specific and it is not clear how HD specific methylation in the brain correlates with the blood compartment, which represents a much more clinically accessible sample. Therefore, we explored the presence of HD specific DNA methylation patterns in whole blood on a cohort of HD mutation carriers and healthy controls from Slovenia. We compared CpG site-specific DNA methylation in whole blood of 11 symptomatic and 9 pre-symptomatic HD mutation carriers (HDM), and 15 healthy controls, by using bisulfite converted DNA on the Infinium®Human Methylation27 BeadChip microarray (Illumina) covering 27,578 CpG sites and 14,495 genes. Of the examined 14,495 genes, 437 were differentially methylated (p<0.01) in pre-symptomatic HDM compared to controls, with three genes (CLDN16, DDC, NXT2) retaining statistical significance after the correction for multiple testing (false discovery rate, FDR<0.05). Comparisons between symptomatic HDM and controls, and the comparison of symptomatic and pre-symptomatic HDM further identified 260 and 198 differentially methylated genes (p<0.01), respectively, whereas the comparison of all HDM (symptomatic and pre-symptomatic) and healthy controls identified 326 differentially methylated genes (p<0.01), however, none of these changes retained significance (FDR<0.05) after the correction for multiple testing. The results of our study suggest that methylation signatures in the blood compartment are not robust enough to prove as valuable biomarkers for predicting HD progression, but recognizable changes in methylation deserve further research.